"We don't really have cause to discuss these things, they don't affect us": a collaborative model for developing culturally appropriate sexual health services with the Bangladeshi community of Tower Hamlets. Issue 2 (30th March 2005) - Beck, A; Majumdar, A; Estcourt, C; Petrak, J
Abstract : Objective: To identify barriers to accessing sexual health care among the Bangladeshi community of east London and to develop a model of community participation in service development. Methods: Qualitative study using one to one interviews with sexual health service users plus focus groups in community settings. Results: 58 people participated in the study, 12 in individual interviews and the remainder in six focus groups. All were of Bangladeshi origin. Four main themes were reported as impacting on access to services; confidentiality concerns, relevance of services to the community, problems with discussing sexual issues, and problems with previous experiences of health promotion. Community values regarding sex outside of marriage were an important underlying factor in participants' responses. Existing sexual health services were seen as culturally insensitive by patients and community groups. Conclusions: Community based health initiatives among hard to reach ethnic minority groups should use existing networks of statutory and non-statutory groups to benefit from local expertise and relationships. Steering groups composed of members of the local communities served by the clinic can usefully inform service development.